Classroom Process and Learning Achievement of MLE and Non-Mle Schools of Keonjhar District - Dr. Ranjan Kumar Rout, (International Journal of Scientific Research and Management (IJSRM), 2021)
NEP, 2020 remarks that a person educated in one’s language, culture, and traditions is not a detriment but indeed a huge benefit to educational, social, and technological advancement. Understanding the relevance of mother tongue as the medium of learning for linguistic minority groups, government of Odisha has introduced Multi Lingual System of Education as a pilot basis from 2006-07 with a view to achieve equitable quality education. To know the ground realities of MLE programme for Juanga learners in terms of classroom process, assessment process and achievement levels the present study was undertaken. The present study comes under the purview of cross‐sectional research design and undertaken through case study approach.  Through purposive sampling technique the researcher selects one MLE and one Non-MLE school from Banspal block of Keonjhar district in Odisha. From these schools all class-III tribal learners and all the teachers were selected purposefully and incidentally respectively.  Three self made tools i.e. Classroom Observation Schedule, Achievement Test (Juanga Language) and Achievement Test (Odia Language) were used in this study.  The data was analysed and interpreted through qualitative data analysis technique, percentage analysis technique. The present study reveals that introduction of MLE in the tribal school has created a good classroom climate in the school so far as activeness of the learners, classroom management, and presentation of learning experiences is concerned. The achievement level in language is upto mark in MLE schools due to the effect of MLE programm. Key words: Classroom Process, Learning Achievement, Multilingual Education